Application of Photoactive Nanomaterials in Degradation of Pollutants - Comparelli, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Photoactive nanomaterials have been receiving increasing attention due to their potential application in the light-driven degradation of water and gas-phase pollutants. However, to exploit the great potential of photoactive materials and access their properties requires fine-tuning of their size/shape-dependent chemical–physical properties, and on the ability to integrate them in photoreactors or to deposit them onto large surfaces. Therefore, the synthetic approach as well as post-synthesis manipulation could strongly affect the final photocatalytic properties of the nanomaterial. The aim of the present Special Issue is to report on the most recent progress towards the application of photoactive nanomaterials and nanomaterial-based coatings in pollutant degradation, paying particular attention to cases close to real application: scalable synthetic approaches to nanocatalysts, preparation of nanocatalyst-based coatings, degradation of real pollutants and bacterial inactivation, and application in building materials.